Detection of parasites in food and water matrices by shotgun metagenomics: A narrative review - Paolo Vatta; Simone M. Cacciò (Food and Waterborne Parasitology)
Many helminths and protozoa are transmitted to humans through the consumption of contaminated food or water, and this underlines the importance of methods for their detection in these matrices. Due to the difficulties in isolating parasites prior to their identification, indirect detection methods are used, mostly relying upon targeted amplification of nucleic acids via PCR and/or qPCR. With the development of high throughput sequencing technologies, an untargeted detection method, shotgun metagenomics, became available. By sequencing the total DNA extracted from a given source, and through bioinformatics analyses of the sequencing reads, shotgun metagenomics allows profiling the entire microbial community therein present, including eukaryotes and, therefore, parasites. In this article, we reviewed the studies that specifically addressed the detection of parasites in food (n = 2) and water matrices (n = 10) by shotgun metagenomics. Most studies focused on wastewater samples and reported the detection of many parasites of human and veterinary importance from various areas of the world, highlighting the potential of shotgun metagenomics to provide important data for parasitic pathogens surveillance. After examining the different analytical workflows employed in these studies, which were not developed for detection of eukaryotes (or parasites), we identified two aspects deserving attention. First, that assignment based on short reads matching ribosomal sequences may generate false positives due to high sequence conservation among eukaryotic organisms. Second, that reassessing the relatively small number of reads of eukaryotic origin by a BLAST search can confirm, or deny, identification of parasitic pathogens.